Désir d’un renouveau pédagogique - David Cascaro (In Situ)
Ordering a ceramic decor for the façade of the new arts and crafts school in Strasbourg, which was built in 1892, was an opportunity to reconsider the questions raised by the Art nouveau movement at the end of the nineteenth century. Developed away from the major capital cities, this trend was caught between the conflicting demands of rejecting academism, returning to manual and regional-based arts, a desire to make art a part of daily life and also to nurture the arts industries and to transform their technical innovations. The young director of the school, Anton Seder, a decorative painter from Munich and also an experienced teacher, persuaded the city of Strasbourg to build a new building to house the school which was intended to improve the quality of regional arts and crafts.Driven by a doctrine based around nature, he gave Léon Elchinger, a talented student from a family of traditional potters in Soufflenheim, the opportunity to create that fresco. Designed and created to simultaneously fulfill the functions of decor, image and heritage, it reveals the ambiguities of Art nouveau, torn as it is between historicism and a fascination with nature. It also illustrates a new pedagogy based on working in workshops and a belief in the possibility of moving beyond set styles through the observation of plants. Finally, it reveals the complex relationships between decor and architecture in the huge Neustadt worksite in Strasbourg and in the context of emerging modernity.